Empowering women through alternative sustainable livelihood: a case study of ornamental fish farming in India - Bhattacharya, Shreya; Das, Basanta Kumar; Ekka, Anjana; Parida, Pranaya Kumar; Roy, Aparna; Lianthuamluaia, Lianthuamluaia; Chakraborty, Sangeeta; Saha, Avishek (Frontiers in Sustainable Food Systems, 2025)
Backyard ornamental fish farming provides positive economic returns to many of the rural poor and empowers them socially and financially. To achieve the national goal of Pradhan Mantri Matsya Sampada Yojana (PMMSY) and to promote the development of the Ornamental Fish Industry, ICAR-Central Inland Fisheries Research Institute is working in a mission mode to empower and encourage tribal and Scheduled Caste women to augment self-employment opportunities. The process operates cyclically, including selecting beneficiaries, capacity building, site-specific demonstration, providing inputs, monitoring the farming activities and establishing marketing linkage. Within 5–6 months of fish rearing, women started their first earnings of ₹ 500-1000/month and enhanced their income continuously. Around 58% of the female ornamental beneficiaries established their ornamental farming unit after the ICAR-CIFRI intervention. Women of all ages are motivated to adopt sustainable ornamental fish farming activities with first-hand live-bearers and hand holdings supply. Women said that lack of proper market accessibility is the main constraint for their viable growth, This type of approach is an initiative toward SDG increasing family happiness index, reducing migration of laborers and empowering socially and economically backward downtrodden communities in the rural sector, which would help boost their livelihood and economic security.